HABITUATION OF DISCIPLINARY CHARACTER IN THE SANTRI LEARNING MODEL TO SUPPORT CRITICAL THINKING POWER (CASE STUDY OF AN-NAJAH ISLAMIC BOARDING SCHOOL DENANYAR JOMBANG) - Maslakha, Hidayatul; Nuha, Muhammad Ullin (Proceeding of International Conference of Islamic Education, 2024)
Islamic boarding schools have a unique education and teaching system. The aim of education at Islamic boarding schools is not only to provide students with education and knowledge, but also to build good character and morals. Some popular learning techniques, as we know, are lectures, discussions, demonstrations, recitations, discovery, inquiry, and so on.  Some traditional Islamic boarding schools (salafiyah) still use the bandongan, sorogan, and shawir or deliberation methods. This method is considered effective for teaching and learning. The result of this research is that there is a disciplined learning habit for students, because learning is well structured, able to create discipline in time and attitude in students. So that students can get used to carrying out habits in the form of learning as they should so that learning achievements or targets can be maximized. A good learning target is to create students who are able to think critically, think critically which is useful in reading, writing, speaking, listening, discussing, problem solving and so on. This can work well if students also carry out the learning process in their learning maximally.